2015
DOI: 10.1155/2015/829680
|View full text |Cite
|
Sign up to set email alerts
|

Music Engineering as a Novel Strategy for Enhancing Music Enjoyment in the Cochlear Implant Recipient

Abstract: Objective. Enjoyment of music remains an elusive goal following cochlear implantation. We test the hypothesis that reengineering music to reduce its complexity can enhance the listening experience for the cochlear implant (CI) listener. Methods. Normal hearing (NH) adults (N = 16) and CI listeners (N = 9) evaluated a piece of country music on three enjoyment modalities: pleasantness, musicality, and naturalness. Participants listened to the original version along with 20 modified, less complex, versions create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
2
29
0
3
Order By: Relevance
“…Alternatively, the noise reduction algorithm may have increased the complexity of the signal through frequent short attenuations of musical notes. This increase in complexity is known to diminish music enjoyment (13,14). Furthermore, the dynamic, constantly varying way in which the noise reduction algorithm attenuates various frequency channels could potentially lead to disturbances that create a more negative music listening experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the noise reduction algorithm may have increased the complexity of the signal through frequent short attenuations of musical notes. This increase in complexity is known to diminish music enjoyment (13,14). Furthermore, the dynamic, constantly varying way in which the noise reduction algorithm attenuates various frequency channels could potentially lead to disturbances that create a more negative music listening experience.…”
Section: Discussionmentioning
confidence: 99%
“…A study in CI users with a MED-EL device on one side and a Cochlear Nucleus on the other found no significant difference in music enjoyment when either device type was used exclusively (12). Recently, we have shown that the novel strategy of re-engineering the original piece of music by either reducing the complexity of music by decreasing the number of musical instruments or minimizing reverberation can increase music enjoyment (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Kohlberg et al similarly showed that reengineering of a piece to include fewer musical elements (vocals, piano, guitar, fiddle, snare) enhanced enjoyment in CI listeners compared to normal-hearing listeners. 11 Simplifying more technical aspects of music also seems to positively affect enjoyment in CI listeners. A study by Certo et al demonstrated that minimization of reverberation time increased music enjoyment under CI conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Complexity reduction was achieved by extracting vocals/bass/drums from stereo recordings and attenuating the other instruments with an adjustable attenuation parameter. A similar approach to reduce music complexity by remixing the music was described in [4] and [5]. In [6] a different approach to reduce (spectral) complexity was investigated in order to increase melody clarity and ease of listening for CI users in instrumental music with reduced-rank approximations of music signals.…”
Section: Introductionmentioning
confidence: 99%